Environmental Risk Mitigation Coaxing a Market in the Battery and Energy Supply and Storage Industry - Weiss, Barbara; Obi, Michiyo (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
IX, 280 p. 24 illus., 22 illus. in color.